Left crural hernia post aortobifemoral by-pas - Croci, Fabio; Rocca, Guillermo; Pérez Penco, Ernesto; Rabellino, Joaquín (Cirugía del Uruguay, 1985)
Description of a case of crural hernia post aortobifemoral by-pass, in a patient that had been operated of an homolateral crural hernia, which is an exceptional occurrence in this veriety of hernia. Studied are the pathology and treatment of same.